Mind Mapping vs Semantic Mapping: Which Technique Gives EFL Learners more Benefits in Reading Comprehension? Pemetaan Pikiran vs Pemetaan Semantik: Teknik Mana yang Memberi Lebih Banyak Manfaat bagi Pembelajar EFL dalam Pemahaman Membaca? - Rachman, Dzul; Khatimah, Khusnul (JEES (Journal of English Educators Society), 2018)
This research aimed at comparing mind mapping technique and semantic mapping technique in teaching reading comprehension. It was intended to find out which technique (mind mapping or semantic mapping) was more effective to strengthen the reading comprehension and which technique was more interesting in learning process to the second graders of SMAN 5 Makassar, South Sulawesi, Indonesia. It was an experimental research. There are two classes taken as sample, XI IPA1as experimental 1 class, and XI IPA2 as experimental 2 class. Researcher collected the data through reading test and questionnaire as research instrument. The result revealed that (1) students obtained higher score after being taught under mind mapping technique as opposed to those who studied under semantic mapping technique (2) students who studied narrative text under mind mapping technique showed great reading interest.